Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙØ¯ÙØ±ÙØ§ ÙÙ ØªØ±Ø¨ÙØ© Ø´Ø®ØµÙØ© Ø§ÙØ·ÙØ§Ø¨ - Sagala, Rumadani (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
Personality is a compacted word that easy to say, but it is difficult to be realized. Etymologically, the personality comes from the Latin language which means persona. This word refers to a mask used by actors in classical drama. Personality is also becomes the reflection of attitude and action of a person or a nation which sets its uniqueness from people or other nations. In Islamic educational context, it is as characteristic and Islamic identity. Thus, the religion that carries out the mandate will enhance the personality and noble character. Personality can be fully determined when the research has done and met the scientific criteria. Therefore, the personality can be taught in schools, introduced to the students through their habituation, principles and ethics. In al-Qurâan, it has been mentioned the terms of formation and development of the human personality, some influential factors and the ways to solve the problems. Muslims as well as believers from the perspective of Islam are those who always train their heart and are not easily get angry but they should be generous, obey Allah, SWT.